Reply to comment on "Kinematic variations across Eastern Cordillera at 24°S (Central Andes): Tectonic and magmatic implications" - Acocella, V. (2009)
We discuss in detail all the comments made by Petrinovic et al., showing that these are not pertinent to the aim of our study, or based on incomplete information of fault kinematics, or unsupported. Despite our limited amount of data, not any of the raised arguments can be seriously taken into account to alter the proposed scenario. Therefore, we demonstrate that our paper is neither "largely speculative" nor "contains major flaws". In particular, the limited evidence of pre-Miocene deformation on a part of a proto-Eastern Cordillera does not affect our interpretation. In fact, our aim was not to reconstruct the tectonic history of Eastern Cordillera, identifying any pre-Miocene episode. Rather, it was to define the kinematics of the largest structures affecting its recent evolution. Therefore, the interesting structures described by Petrinovic et al., also kinematically poorly constrained, cannot give useful insights, simply because the aim and time frame of our study are different.